Portrait of attendees at convention for the California Industrial Education Association - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the annual California Industrial Education Association Convention, held April 23-24, 1948 in San Jose, California.